MUNICIPAL BUDGETING IN WARTIME. - Tenner, Irving (The Accounting Review, 1943)
Budgeting involves both planning and estimating processes which present problems even during peace time. During a period of war these problems are magnified by rapid changes in conditions which make accurate forecasting difficult, if not impossible. However, many of the conditions and the budget problems to which they give rise can be anticipated. Not all municipalities will fare alike and allowance will therefore have to be made for individual circumstances. Decreases in revenues from property taxes, licenses and permits, some state shared taxes and grants-in-aid can be expected. The assessed valuation of both real and personal property will decrease. Real property assessed values will decrease because the depreciation of property as a result of wear and tear, its destruction by fire or other causes, and the reduction in its value caused by obsolescence are not being offset by new building construction. Again, increased holdings of property by the Federal government mean increased exemptions.